2014
DOI: 10.1111/joic.12149
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Outcomes of Successful Chronic Total Occlusion Percutaneous Coronary Interventions Using the Antegrade and Retrograde Approach

Abstract: Retrograde CTO PCI was associated with higher incidence of TLR, but similar incidence of death and myocardial infarction compared to antegrade CTO PCI. These findings likely reflect the higher complexity of CTO lesions treated with the retrograde approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 36 publications
2
20
0
2
Order By: Relevance
“…Although the long- term implications of PMI remain the subject of debate, they were associated with worse clinical outcomes in one study [12]. Use of the retrograde approach has been associated with worse outcomes as compared with the antegrade approach in one study [1]. A recent analysis from the European Registry of CTO interventions (ERCTO) showed favorable outcomes with the retrograde approach [8].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Although the long- term implications of PMI remain the subject of debate, they were associated with worse clinical outcomes in one study [12]. Use of the retrograde approach has been associated with worse outcomes as compared with the antegrade approach in one study [1]. A recent analysis from the European Registry of CTO interventions (ERCTO) showed favorable outcomes with the retrograde approach [8].…”
Section: Discussionmentioning
confidence: 98%
“…Percutaneous coronary intervention (PCI) of chronic total occlusions (CTOs) has undergone remarkable evolution in both equipment and technique, resulting in high success and low complication rates [1][2][3][4]. There are three major CTO crossing strategies: [1] antegrade wire escalation, [2] antegrade dissection/re-entry, and [3] the retrograde approach.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,[6][7][8] Crossing strategy selection depends heavily on the angiographic characteristics of the occlusion, 9 but a critical factor in clinical decision making is long-term patency. Although early reports on extensive antegrade dissection/re-entry techniques suggested high restenosis rates, 10-13 limited contemporary data have been published in this area, [14][15][16] prompting us to examine patients treated at our institution during the past 3 years, during which maturity was reached with the use of various crossing techniques.…”
mentioning
confidence: 99%
“…Current studies have shown that successful percutaneous coronary intervention (PCI) for chronic total occlusion (CTO) improves the quality of life, left ventricular ejection fraction and survival rate [1][2][3][4][5][6][7][8]. The development of devices such as guide wires, balloons and stents, and the improvement of operator techniques has increased the success rates of PCI for CTO lesions and decreased the complication rates over time [9,10].…”
Section: Introductionmentioning
confidence: 99%